SdiA Improves the Acid Tolerance of E. coli by Regulating GadW and GadY Expression - Ma, Xingyan; Zhang, Shebin; Xu, Zhenjie; Li, Honglin; Xiao, Qian; Qiu, Feng; Zhang, Weizheng; Long, Yifei; Zheng, Dexiang; Huang, Bin; Chen, Cha; Lu, Yang (Frontiers in Microbiology, 2020)
The acid tolerance mechanism is important for Escherichia coli to resist acidic conditions encountered in mammalian host digestive tract environment. Here, we explored how the LuxR protein SdiA influenced E. coli acid tolerance ability in the context of the glutamate- and glutamine-dependent acid resistance system (AR2). First, using a growth and acid shock assay under different acid stresses, we demonstrated that the deletion of sdiA in SM10λpir or BW25113 led to impaired growth under the acidic environment of pH 3–6, which was restored by complementary expression of SdiA. Next, transcriptome sequencing and qPCR disclosed that the expression of glutamate decarboxylase W (GadW) and GadY, the key members of the AR2 system, were regulated by SdiA. Further, β-galactosidase reporter assays showed that the promoter activity of gadW and gadY was positively regulated by SdiA. Moreover, qPCR and β-galactosidase reporter assays confirmed that the regulation of SdiA on GadW, but not GadY, could be enhanced by quorum sensing (QS) signal molecules AHLs. Collectively, these data suggest that SdiA plays a crucial role in acid tolerance regulation of E. coli. Our findings provide new insights into the important contribution of quorum sensing system AHLs–SdiA to the networks that regulate acid tolerance.